Efeito do 3,4-dibutiril-D-quiroinositol na disfunção endotelial da Diabetes Mellitus - Lessa, Lucília Maria Abreu (2005)
Endothelial dysfunction (ED) is an early common feature of diseases with cardiovascular risk, including diabetes. Hyperglycemia and hyperlipidemia clearly are causative factors. Recently excessive mitochondrial superoxide (ROS) production with hyperglycemia and hyperlipidemia was also shown to be a key mechanistic event rclated to diabetic cornplications. Inositol components of a putative insulin inositol glycan mediator namely, D-chiro-inositol (DCI) have demonstrated in vivo insulin-like metabolic effects. We tested the hypothesis that the its soluble derivative 3,4-dibutyryl D-chiro-inositol (db-DCI) woiild prevení or reverse ED in 4-week alloxan-diabetic rats and rabbits. We also compared the effect of db-DCI with the actions of myoinositol (myo-lNS) (cndogcnous inositol). Endothclium-dcpcndent versus cndothcliumindependent relaxations of aortic rings, arteriolar mesenteric beds of rats and aortic rings and kidneys of rabbits were examined. The administration of db-DCI orally reduced hyperglycemia and hypertriglyceridemia (HTG) to 31,1±3,7% e 60,9±5,8%, respectively. Chronic oral administration prevented ED in rat aortic rings and arteriolar mesenteric beds. Acute db-DCI administration in vitro (one hour), to all diabetic tissues studied reversed ED. The relaxation induced by Ach and NO was potentiated in aortic rings. Potentiation of nitric oxide (NO) relaxation by superoxide dismutase (SOD) and by inositois was also demonstrated in diabetic tissues. Two inositois DCI and db-DCI were tested for their ability to decrease elevated ROS generated by incubation of endothelial cells in high glucose. They were effective dose dependently at low micromolar concentrations. The reduetion of nitro blue tetrazolium (NBT) by superoxide generated by the xanthine/xanthine oxidase system was also evaluated in the presence of SOD or the db-DCI. The inositol prevented NBT reduetion with dbDCI more efficacious than the myo-INS. Histochemical examination of aortic rings for protein SNO and nitrotyrosine demonstrated a decrease in diabetic rings for protein SNO and nitrotyrosine demonstrated a decrease in diabetic rings and a restoration with administered db-DCI. In summary, all inositois tested prevented and reversed ED in rat and rabbit conductance and resistance vessels, reducing RS in endothelial cells and preserving NO signaling. These positive effects are probably related to both their metabolic and antioxidant scavenging activities. Of each inositois tested db-DCI was the most effective.